Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1055/s-0035-1549964
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine Impairs Insulin Secretion without Modifying Extracellular Serotonin Levels in MIN6 β-cells

Abstract: The inhibitory effect of fluoxetine on β-cell glucose stimulated insulin secretion is not mediated by blockage of 5HT transporter through SERT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 30 publications
(44 reference statements)
5
19
0
Order By: Relevance
“…More recent studies confirm that 5‐HT is released along with insulin and ATP from β‐cells and/or released from a subset of islet cells and that secretion of 5‐HT is regulated by increased glucose concentrations in MIN6 β‐cells, as well as in human islets . However, a basal leakage or constitutive release of 5‐HT is most likely also present, as indicated by a high basal efflux of 5‐HT in mouse islet and MIN6 β‐cells loaded with 5‐HTP . Additionally, the turnover rate of 5‐HT in mouse islets and MIN6 β‐cells is estimated to be 2 hours, suggesting a rapid clearance of the amine.…”
Section: Introductionmentioning
confidence: 89%
“…More recent studies confirm that 5‐HT is released along with insulin and ATP from β‐cells and/or released from a subset of islet cells and that secretion of 5‐HT is regulated by increased glucose concentrations in MIN6 β‐cells, as well as in human islets . However, a basal leakage or constitutive release of 5‐HT is most likely also present, as indicated by a high basal efflux of 5‐HT in mouse islet and MIN6 β‐cells loaded with 5‐HTP . Additionally, the turnover rate of 5‐HT in mouse islets and MIN6 β‐cells is estimated to be 2 hours, suggesting a rapid clearance of the amine.…”
Section: Introductionmentioning
confidence: 89%
“…The MIN6 cell line is a well-established, time honored, model for the study of pancreatic β-cell function (Miyazaki et al, 1990;Ishihara et al, 1993;Daunt et al, 2006;Cataldo et al, 2015). The main advantage of a cell line for pancreatic β-cell research is that it large numbers of phenotypically homogenous cells are available which are devoid of paracrine and neuroendocrine effects that arise from interaction with the other endocrine and neuronal cell types that reside within the pancreatic islet (Ishihara et al, 1993).…”
Section: Cellsmentioning
confidence: 99%
“…Pancreatic β-cells secrete 5-HT which may exert autocrine effects (Bennet et al, 2015). However, an involvement of SERT for the cytotoxic effects of these ADs can be dismissed, since β-cells do not express the Slc64a gene that encodes for SERT nor do ADs affect the release of 5-HT from them (Cataldo et al, 2015) .…”
Section: The Effects Of the Ads Are Not Mediated By Blockade Of Serotmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that chronic treatment of INS-1E β cells with fluoxetine (1 μM) impaired GSIS and increased the production of reactive oxygen species (ROS) resulting in damage to mitochondrial function 10 . Moreover, fluoxetine-induced impairment of GSIS observed in β cell lines may be independent of accumulation of extracellular 5-HT level 11 .…”
Section: Introductionmentioning
confidence: 97%